2022
DOI: 10.3389/fonc.2022.947054
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis reveals DDX21 as a potential biomarker for the prognosis of multiple tumor types

Abstract: BackgroundDExD-box helicase 21 (DDX21) is an essential member of the RNA helicase family. DDX21 is involved in the carcinogenesis of various malignancies, but there has been no comprehensive research on its involvement in different types of cancer.MethodThis study used TCGA, CPTAC, GTEx, GEO, FANTOM5, BioGRID, TIMER2, GEPIA2, cBioPortal, STRING, and Metascape databases and Survival ROC software to evaluate DDX21 gene expression, protein expression, immunohistochemistry, gene mutation, immune infiltration, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…[30] Hu Ankang et al also found that DDX21 gene was significantly expressed in 13 cancers including CRC. [31] The above literature review is consistent with our results. The higher the expression of DDX21 in CRC, the higher the DDX21, the worse the prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…[30] Hu Ankang et al also found that DDX21 gene was significantly expressed in 13 cancers including CRC. [31] The above literature review is consistent with our results. The higher the expression of DDX21 in CRC, the higher the DDX21, the worse the prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…We identified 2831, 3183 and 3090 protein groups in GC, HRS and SLL populations, respectively ( Figure 2A-B, Supplementary figure 2C-D ). Comparing HRS or SLL to GC, the top ten significantly differentially expressed proteins, nine of them have previously been linked to lymphoma: TUBB2A, KPNA2, CDK1, IRF4, FSCN1, DDX21, TSR1, collagen and C1QA ( Figure 2A-B ) 15, 16, 17, 18, 19, 20, 21, 22, 23 . Furthermore, upregulation of SLC3A2 in SLL was in alignment with data from the Human Protein Atlas (HPA) database 24 ( Supplementary figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there has been growing interest in identifying new biomarkers for EC. Several studies have focused on identifying and characterizing the roles of novel oncogenes in EC progression and prognosis [14][15][16][17]. For instance, OTU deubiquitinase, ubiquitin aldehyde binding 2 (OTUB2) expression was significantly enhanced in EC, which was associated with poor prognosis of cancer patients.…”
Section: Discussionmentioning
confidence: 99%